Knee biomechanics of patients with total knee replacement during downhill walking on different slopes - Chen Wen; Harold E. Cates; Joshua T. Weinhandl; Scott E. Crouter; Songning Zhang (Elsevier, 2022)
Purpose: The purpose of this study was to compare knee biomechanics of the replaced limb to the non-replaced limb of total knee replacement (TKR) patients and healthy controls during walking on level ground and on decline surfaces of 5°, 10°, and 15°. Methods: Twenty-five TKR patients and 10 healthy controls performed 5 walking trials on different decline slopes on a force platform and an instrumented ramp system. Two analyses of variance, 2 × 2 (limb × group) and 2 × 4 (limb × decline slope), were used to examine selected biomechanics variables. Results: The replaced limb of TKR patients had lower peak loading-response and push-off knee extension moment than the non-replaced and the matched limb of healthy controls. No differences were found in loading-response and push-off knee internal abduction moments among replaced, non-replaced, and matched limb of healthy controls. The knee flexion range of motion, peak loading-response vertical ground reaction force, and peak knee extension moment increased across all slope comparisons between 0° and 15° in both the replaced and non-replaced limb of TKR patients. Conclusion: Downhill walking may not be appropriate to include in early stage rehabilitation exercise protocols for TKR patients.